Morphological changes in bone tissue in conditions of a modelled traumatic injury of the tibial diaphysis in rats - Pobel, Yevgeny; Dedukh, Ninel; Malyshkina, Svitlana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Morphological and morphometric studies of distal tibial diaphyses in 21 rats after a modelled transcortical through perforated defect of the diaphysis and its fracture were carried out. Qualitative and quantitative data about characteristics of the compact and trabecular bone in the proximal and distal metaphyses were received. It was found out that both a low-intensity injury (a transcortical perforated defect) and a fracture affected the bone tissue state in the metaphyses. The most evident post-traumatic osteopoenic changes in the trabecular and compact bones were registered in the distal metaphysis after a diaphyseal fracture.